The Adjustment of Employment Concept in Paying Wages Under Minimum Wage Provisions For Restorative Justice - Terubus Terubus (Universitas Negeri Semarang, 2024)
The purpose of this study is to analyze and find the concept of adjustment in employment cases in terms of paying wages below the minimum wage from a restorative justice perspective. This research is normative legal research. This research uses a legal approach, a conceptual approach, and a philosophical approach. The results show that the concept of resolving labor cases in terms of paying wages below the minimum wage is realized through a peace agreement with victim-offender mediation (VOM) while involving the responsibility of criminals in recovering losses due to criminal acts. Concrete evidence of recovery for victims is started in an agreement that is agreed upon and signed by the parties so that it has legal validity and reasons and has legal force in protecting the interests and rights of the parties.